A CORRELATIONAL ANALYSIS OF CARDIAC AUTONOMIC NEUROPATHY, ARTERIAL STIFFNESS, AND LIPID PROFILE IN DIABETIC PATIENTS - Santosh Kumar; Neera Kumari (Student's Journal of Health Research, 2023)
Objective: It is necessary to comprehend the mechanistic connections between cardiovascular risk factors. This is the foundation for the present investigation. Materials and Methods: In the cross-sectional and observational research, patients with T2DM aged 53 to 62 years and age- and gender-matched healthy control subjects were recruited (n = 30 each, eight women). After obtaining the participants' consent, anthropometric measurements, physiological parameters including resting heart rate, peripheral blood pressure (PBP), central blood pressure (CBP), augmentation index% (AIx%), brachial-ankle pulse wave velocity, and lead II ECG for analysis of heart rate variability parameters were obtained. In addition, the lipid profile and fasting blood glucose were evaluated. Results: In T2DM patients, peripheral systolic blood pressure was significantly higher (P = 0.05). Patients with T2DM demonstrated dyslipidemia. In T2DM patients, the atherogenic index of plasma (AIP) was also significantly higher. The AIP index was discovered to have a negative association with HF. Multiple regression analysis identifies serum TG, high-density lipoprotein cholesterol (HDL-C), and AIP index as independent predictors of T2DM vasculopathy. Conclusion: Atherogenic dyslipidaemia was observed in T2DM patients in conjunction with elevated serum levels of TG, VLDL-C, and decreased serum levels of HDL-C in the present study. In addition, the AIP index, a predictor of cardiovascular risk, was significantly greater in T2DM patients. In these patients, dyslipidaemia was discovered to be associated with dysregulation of the autonomic nervous system. Recommendation: Recommendations for the treatment of CAN include early optimization of blood glucose regulation to avoid or delay the development of CAN in people with T1DM.